Teachers' readiness in utilizing educational portal resources in teaching and learning - Mahmud, Rosnaini; Ismail, Mohd Arif; Abdul Rahman, Fadzilah; Kamarudin, Nurzatulshima; Ruslan, Aisyatul Radhiah (Elsevier, 2012)
The purpose of this study was to identify teachers’ readiness in utilizing the educational resources from the Eduwebtv online portal. Teachers’ readiness was measured in terms of knowledge, skills and attitude. Research samples consisted of 387 secondary school teachers from five different states selected using the cluster simple random sampling technique. The design of the study was quantitative in nature employing the survey method. Data were gathered through the use of the Eduwebtv ReadinessQuestionnaire developed by the researchers. The questionnaire was divided into four sections a) background information, b) knowledge of Eduwebtv, c) skills in using Eduwebtv, and d) attitude towards using Eduwebtv. Data were analyzed using descriptive statistics of mean, frequency, percentage and standard deviation. Findings revealed that majority of the teachers had moderate (n=201, 51.9%) to high (n=186, 48.1%) levels of knowledge of Eduwebtv as an educational resource portal. Also found majority of the teachers had moderate skills in using Eduwebtv portal. Apart from this, majority of the teachers were found to foster positive attitudes towards the use of Eduwebtv online resources for teaching and learning. In terms of readiness in utilizing the Eduwebtv portal, these findings suggest that although teachers have knowledge of Eduwebtv and its benefits to both teachers and students, they seem lacking in the skills to fully capitalize on the advantages afforded by this online technology.